EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION TERHADAP KEAKTIFAN BELAJAR PESERTA DIDIK PADA MATA PELAJARAN AQIDAH AKHLAK - Refty Ani Arum Daty; Guntur Cahaya Kesuma; Uswatun Hasanah (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
This study examines the effectiveness of the Group Investigation (GI) cooperative learning model in improving students’ learning activeness in Aqidah Akhlak at MTs NU Pesisir Tengah. The research was motivated by low student participation, indicated by limited involvement in discussions, reluctance to express opinions, and a less conducive classroom environment. A quantitative approach using a Posttest-Only Control Group Design was applied to two seventh-grade classes selected through simple random sampling: an experimental class using GI and a control class using conventional learning. Data were collected through a learning activeness questionnaire consisting of 15 valid and reliable items (α = 0.87). Data analysis included normality, homogeneity, and independent t-tests. The results show that the GI model significantly increased students’ learning activeness, especially in active problem-solving and collaborative participation. Students demonstrated higher engagement through group discussions, planning strategies, and presenting investigation results. The novelty of this research lies in applying GI within Aqidah Akhlak learning at Islamic junior high schools, emphasizing both active learning and the internalization of moral values. These findings highlight the importance of student-centered and collaborative strategies in creating participatory and meaningful learning environments. This study contributes theoretically and practically by providing an innovative instructional model that integrates cooperative learning with moral development in Islamic education contexts.